Enhancing Science Teachers' Competence Through Comprehensive Chemistry Material: Peningkatan Kompetensi Guru IPA Melalui Pendalaman Materi Kimia - Said, Irwan; Ningsih, Purnama; Hamzah, Baharuddin; Reny, Reny (Yayasan Ahmar Cendekia Indonesia, 2024)
The low performance of science teachers in learning chemistry material at SMP Negeri 17 Palu is caused by the density of material and the lack of supporting facilities as well as the limitations of teacher professionalism, especially for those with a background in physics and biology education. This problem occurs not only at SMP Negeri 17 Palu, but also at SMP Negeri 16 Palu. Intervention is therefore necessary to enhance the quality of science learning. FKIP Tadulako University implemented an in-depth chemistry material program for science teachers at SMP Palu Utara and Tawaeli with the goal of improving their professional and pedagogical competence. Subject teachers actively participated in this program, applying the principles of cooperative and mutual learning. The evaluation showed a significant increase in teachers' understanding of chemistry concepts and the application of active learning strategies in the classroom. The stages of the activity include material identification, in-depth study of the material, preparation of RPP or teaching modules, and evaluation of the results. The school's full support and the enthusiasm of the participants contributed to the success of this program, with plans to continue advanced training with more specific material. Abstrak Rendahnya kinerja guru IPA dalam pembelajaran materi kimia di SMP Negeri 17 Palu disebabkan oleh padatnya materi dan kurangnya fasilitas pendukung serta keterbatasan profesionalisme guru, terutama bagi mereka yang berlatar belakang pendidikan fisika dan biologi. Masalah ini tidak hanya terjadi di SMP Negeri 17 Palu, tetapi juga di SMP Negeri 16 Palu. Oleh karena itu, diperlukan intervensi untuk meningkatkan kualitas pembelajaran IPA. FKIP Universitas Tadulako melaksanakan program pendalaman materi kimia bagi guru-guru IPA di SMP Palu Utara dan Tawaeli, dengan tujuan meningkatkan kompetensi profesional dan pedagogik mereka. Program ini dilakukan secara berkelanjutan dengan melibatkan guru mata pelajaran dan menerapkan prinsip-prinsip pembelajaran kooperatif dan mutual learning. Evaluasi menunjukkan peningkatan signifikan dalam pemahaman guru terhadap konsep-konsep kimia dan penerapan strategi pembelajaran aktif di kelas. Tahapan kegiatan meliputi identifikasi materi, pendalaman materi dan penyusunan RPP atau Modul Ajar, serta evaluasi hasil. Dukungan penuh dari pihak sekolah dan antusiasme peserta berkontribusi pada keberhasilan program ini, dengan rencana untuk melanjutkan pelatihan lanjutan dengan materi yang lebih spesifik.